Density functional theory calculation for understanding the roles of biochar in immobilizing exchangeable Al3 + and enhancing soil quality in acidic soils - Debo He; Xinyi Liu; Dongni Hu; Ping Lei; Jinbo Zhang; Zhixin Dong; Bo Zhu (Ecotoxicology and Environmental Safety)
Soil acidification poses a significant threat to agricultural productivity and ecological balance. While lime is a common remedy, it can have limitations, including nutrient deficiencies and potential soil compaction. Therefore, exploring alternative and sustainable amendments is crucial. This study investigated the efficacy of biochar as a substitute for lime in reducing soil acidification and improving soil quality. Through incubation experiments, we compared the effects of biochar and lime on soil properties. Additionally, we employed density functional theory (DFT) calculations to elucidate the mechanisms underlying biochar's ability to immobilize exchangeable Al3+. Furthermore, we conducted 15N double-labeled incubation experiments to examine the impact of biochar on soil nitrogen (N) transformation in acidic conditions. Our results indicated that biochar was as effective as lime in enhancing soil quality and mitigating acidification. Soils developed from the Jurassic Shaximiao Formation (J2s) purple mudstone with 3 % biochar addition exhibited a 31.15 % and 17.43 % increase in total N compared to soils treated with 0.1 % and 0.2 % lime, respectively. Similarly, soils developed from the Cretaceous Jiaguan Formation (K2j) purplish red sandstone with 1 % and 3 % biochar addition showed a 38.75 % and 64.30 % increase in soil organic carbon compared to soils treated with 0.2 % lime. DFT calculations revealed that biochar's functional groups exhibited a stronger affinity for immobilizing exchangeable Al3+ than other soil cations. This preferential adsorption was attributed to the stronger interaction and higher bond dissociation energy between biochar functional groups and Al3+. These findings collectively highlight the potential of biochar as a sustainable and effective amendment to reduce Al toxicity in acidic soils, thereby promoting soil quality and sustainable agricultural and ecological practices.